Pengaruh Kepemimpinan Pelayanan, Kecerdasan Emosional Dan Komunikasi Interpersonal Terhadap OCB Pada Kantor Imigrasi Kelas 1 TPI Padang - Fitriadi, Yohan; Nugraha, Afif (Riset Sinergi Indonesia, 2022)
This study aims to examine the Service Leadership Method, Emotional Intelligence and Interpersonal Communication. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By distributing questionnaires as many as 65 respondents.The results of the data analysis concluded that there was no positive effect between the service leadership variable and the employee job satisfaction variable, and there was no significant effect. There is a big positive impact between the variable